High Performance Low Power Dual Edge Triggered Static D Flip-Flop - Gagandeep Singh; Gurmohan Singh; Vemu Sulochna (Institute of Advanced Engineering and Science, 2013)
In this paper a low-power double-edge triggered static flip-flop (DETSFF) suitable for low-power and high performance applications is presented. The designed DETFF is verified at gpdk 180nm-1.8V CMOS technology. Comparison with some of the latest DETFFs shows that the proposed DETSFF can achieve the lowest power consumption, lowest clock to Q delay and thus Power-delay-product (PDP). Moreover, the proposed DETSFF comprises of only 15 transistors hence require lesser number of transistors and thus requires lesser overall silicon area.DOI:http://dx.doi.org/10.11591/ijece.v3i5.3164